2009
DOI: 10.1007/s00056-009-0744-y
|View full text |Cite
|
Sign up to set email alerts
|

Craniofacial Growth Patterns in Patients with Congenitally Missing Permanent Teeth*

Abstract: This examination demonstrates no statistically-relevant correlation between craniofacial growth pattern and the congenital absence of certain permanent teeth, although horizontal growth is more frequent (but not significant) in patients with congenitally missing second premolars.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
10
1
5

Year Published

2011
2011
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(24 citation statements)
references
References 29 publications
8
10
1
5
Order By: Relevance
“…Based on linear measurements, without calculating any ratio, Lisson and Scholtes [14] reported reduced upper and lower anterior facial heights, whereas Woodworth et al [17] only found a reduction in the upper anterior facial height. However our findings coincide with most authors observations of a reduced lower facial height only [15,18]. The ratio of posterior to anterior facial height (Jarabak index) did not differ from that of standard controls, thus implying a reduction of the posterior facial height to a similar extent to that of the anterior facial height.…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…Based on linear measurements, without calculating any ratio, Lisson and Scholtes [14] reported reduced upper and lower anterior facial heights, whereas Woodworth et al [17] only found a reduction in the upper anterior facial height. However our findings coincide with most authors observations of a reduced lower facial height only [15,18]. The ratio of posterior to anterior facial height (Jarabak index) did not differ from that of standard controls, thus implying a reduction of the posterior facial height to a similar extent to that of the anterior facial height.…”
Section: Discussionsupporting
confidence: 91%
“…The same observation was reported by Bauer et al [18]. The Hasund index increased in the total examination group as well as in each of the three subgroups, obviously regardless of whether hypodontia was present in the mandible the maxilla or both jaws.…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…A very high prevalence of total agenesis of all third molars has also been described. 19 Numerous investigator groups around the world have explored associations between hypodontia and significant alterations in craniofacial morphology in nonsyndromic samples [23][24][25][26][27][28][29][30][31] and craniofacial anomalies such as ectodermal dysplasia 32,33 and Pierre Robin sequence. 34 Whether an association exists between the location of hypodontia and differential alterations in the regional craniofacial morphology in DS is unknown.…”
Section: Introductionmentioning
confidence: 99%